2005
DOI: 10.1128/jvi.79.8.5017-5026.2005
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of Enveloped Double-Stranded RNA Bacteriophages φ13 and φ6 intoPseudomonas syringaeCells

Abstract: Bacteriophages 6 and 13 are related enveloped double-stranded RNA viruses that infect gram-negative Pseudomonas syringae cells. 6 uses a pilus as a receptor, and 13 attaches to the host lipopolysaccharide. We compared the entry-related events of these two viruses, including receptor binding, envelope fusion, peptidoglycan penetration, and passage through the plasma membrane. The infection-related events are dependent on the multiplicity of infection in the case of 13 but not with 6. A temporal increase of host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…Upon the first encounter of a susceptible host, many bacterial viruses initially bind reversibly to the structures on the cell surface and only then commit to the infection by attaching to the cell irreversibly, a stage subsequently followed by delivery of the viral genome into the cell interior (8,21,(43)(44)(45). To test the reversibility of the SIRV2 adsorption, we investigated whether viral particles could be washed off from the host cell surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon the first encounter of a susceptible host, many bacterial viruses initially bind reversibly to the structures on the cell surface and only then commit to the infection by attaching to the cell irreversibly, a stage subsequently followed by delivery of the viral genome into the cell interior (8,21,(43)(44)(45). To test the reversibility of the SIRV2 adsorption, we investigated whether viral particles could be washed off from the host cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of cell surface structures are known to be targeted by viruses. For example, in the case of bacterial viruses, nearly all components of the cell envelope are known to serve as receptors (7), including lipopolysaccharide (8)(9)(10), pili (11)(12)(13), flagella (14)(15)(16)(17), (lipo-)teichoic acids (18)(19)(20), peptidoglycan (21), or various integral membrane proteins (22)(23)(24). The only archaeal virus for which a potential cellular receptor has been identified is Ch1, infecting the hyperhalophilic host Natrialba magadii (25).…”
mentioning
confidence: 99%
“…Indeed, certain types of virus-encoded holins depolarize bacterial cells, typically as a late event (31). In the cases of the double-stranded RNA phages 6 and 13, virus entry is associated with a limited depolarization of the plasma membrane along with a transient increase in permeability of the gram-negative Pseudomonas syringae outer membrane (7). Indeed, nucleocapsid binding of 6 to the plasma membrane is independent of the membrane potential (⌬⌿), yet internalization requires a high ⌬⌿ (34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that bioaerosols can be produced by different units in wastewater treatment plants, such as aeration tanks, grit chambers and trickling filters. [36][37][38] The concentration of airborne bacteria has been shown to vary from as low as 4 to 1000s of CFU m -3 depending on the species. 33,[39][40][41] Airborne viruses have been detected at WWTPs as well.…”
Section: Potential For Aerosol Transmission Via Wastewatermentioning
confidence: 99%
“…MS2 and Phi6 were propagated from stock suspensions according to established methods. 38 The stocks had concentrations of 10 9 -10 11 plaqueforming units per milliliter (PFU mL -1 ). Briefly, 50 L of MS2 stock was mixed with 200 L of overnight cultured E. coli and 4.75 mL of LB soft agar.…”
Section: Aerosolization Of Ebola Virus Surrogates Emission Rates Of mentioning
confidence: 99%